IMPLIKASI LOYALITAS PELANGGAN TERHADAP KEPUASAN PENERBANGAN LION AIR - Suryanto Suryanto; Ivan Roy Hutapea (Jurnal Manajemen FE-UB, 2020)
This study aims to determine the effect of the influence of service quality and trust oncustomer loyalty of Lion Air with customer satisfaction as a mediating variable.The data used in this study are primary data obtained from the distribution ofquestionnaires to passengers who ARE AT Terminal 1B Soekarno Hatta Airport, Cengkareng,Jakarta. The data processing method uses the path analysis method with the help of the SPSSversion 24 program.The results showed that method I: Directly the variables of service quality and trust have apositive and significant effect on customer satisfaction. Method II: Directly the variable servicequality, trust, and customer satisfaction have a positive and significant effect on customerloyalty. Customer satisfaction is able to mediate customer quality towards customer loyalty andcustomer satisfaction is able to mediate trust in customer loyalty using the Sobel Test method.Keywords: service quality, trust, customer satisfaction, customer loyalty